Chancroid: clinical manifestations, diagnosis, and management - Lewis, D (BMJ Group, 2003)
Chancroid is a sexually transmitted disease (STD) caused by the Gram negative bacterium Haemophilus ducreyi and is characterised by necrotising genital ulceration which may be accompanied by inguinal lymphadenitis or bubo formation. H ducreyi is a fastidious organism which is difficult to culture from genital ulcer material. DNA amplification techniques have shown improved diagnostic sensitivity but are only performed in a few laboratories. The management of chancroid in the tropics tends to be undertaken in the context of syndromic management of genital ulcer disease and treatment is usually with erythromycin. A number of single dose regimens are also available to treat H ducreyi infection. Genital ulceration as a syndrome has been associated with increased transmission of human immunodeficiency virus (HIV) infection in several cross sectional and longitudinal studies. Effective and early treatment of genital ulceration is therefore an important part of any strategy to control the spread of HIV infection in tropical countries.